Retribusi Pemakaman Etnis Tionghoa Kota Padang 1989-2016 - Novika Restu Pratiwi; Erniwati Erniwati; Zul Asri (Galanggang Sejarah, 2019)
This article aims to explain the wisdom of the government towards the burial of Chinese ethnicity and the impact of unstable funeral fees. The results of this study were in 1989. The local government of Padang City had provided a burial place for the Chinese in Bungus Teluk Kabung. There were two locations provided by the local government of Padang City, the first was not paying and the second had to pay, but the implementation was not paid is not in accordance with the tradition of Chinese ethnic funerals. Finally, the Chinese chose a place where the location was in accordance with their funeral traditions even though they had to pay. Initially, the paid Chinese cemetery complex was initially paid at a standard price, but after the Local Regulation Number 11 of 2011 was enacted in 2012, the Chinese have difficulty obtaining burial grounds because of the expensive price of the standard 1 x 2 tomb The meter is only Rp125 thousand for one grave, plus the burial fee of Rp375 thousand. This means that for one time the burial rate is only Rp500 thousand. Chinese people tend to spend land reaching 4 x 6 meters or more than 22 square meters. The excess land rates are Rp250 thousand per meter. Therefore, Chinese ethnic funeral levies can reach Rp5 to Rp6 million / two years. As a result, there are changes in the traditions of the Chinese ethnic, where those who initially tend to bury their families so that they choose cremation, because this cremation is considered to reduce costs.